The interpretation of quantum mechanics - Omnès, Roland (Princeton series in physics., 1994)
The interpretation of quantum mechanics has been controversial since the introduction of quantum theory in the 1920s. Although the Copenhagen interpretation is commonly accepted, its usual formulation suffers from some serious drawbacks. Based mainly on Bohr's concepts, the formulation assumes an independent and essential validity of classical concepts running in parallel with quantum ones, and leaves open the possibility of their ultimate conflict. In this book, Roland Omns̈ examines a number of recent advances, which, combined, lead to a consistent revision of the Copenhagen interpretation. His aim is to show how this interpretation can fit all present experiments, to weed out unnecessary or questionable assumptions, and to assess the domain of validity where the older statements apply. Drawing on the new contributions, The Interpretation of Quantum Mechanics offers a complete and self-contained treatment of interpretation (in nonrelativistic physics) in a manner accessible to both physicists and students. Although some "hard" results are included, the concepts and mathematical developments are maintained at an undergraduate level. This book enables readers to check every step, apply the techniques to new problems, and make sure that no paradox or obscurity can arise in the theory. In the conclusion, the author discusses various philosophical implications pertinent to the study of quantum mechanics.